Characteristic of different components development of psychological readiness to professional activities for students with somatic disorders - Serdiuk, Liudmyla; Petruchenko, Nadiia (Social Welfare: Interdisciplinary Approach, 2012)
The paper presents the main results of empirical studies aimed at determining characteristics of psychological readiness to professional activities for students with somatic defects. The study involves 238 students, 96 of them have different physical disabilities. 10 questionnaires and techniques were applied. Results are presented according to an eight-component structure of psychological readiness to professional activities proposed by the authors. The study results are presented in comparison with healthy students’ results as well as in terms of certain indexes dynamics during university learning for various components of psychological readiness. The obtained results can become a basis for psychological activities aimed at such readiness formation.